A rare case of congenital piloleiomyoma of the eyelid. (2nd November 2021) - Alam, Shahid; Banerjee, Prabrisha; Krishnakumar, Subramanian
ABSTRACT: Cutaneous leiomyoma is an infrequently occurring benign smooth muscle neoplasm of skin. Piloleiomyoma, angioleiomyoma, and genital leiomyoma are the three forms of the cutaneous leiomyoma. Piloleiomyoma arises from arrector pili muscle and is commonly seen in the adult population. Congenital piloleiomyoma is extremely rare and has never been reported to arise from the eyelid. We report a case of a neonate presenting with upper eyelid mass lesion since birth causing mechanical ptosis. Incisional biopsy followed by histopathology and immunohistochemistry established the diagnosis of piloleiomyoma. There was associated cryptorchidism in our case, a systemic association that has never been reported. Considering the benign nature of the lesion the child was kept under regular follow up without attempting any further removal.